2019
DOI: 10.3390/w12010004
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Change of Bosten Lake Area in Response to Climate in the Past 30 Years

Abstract: The widely distributed lakes, as one of the major components of the inland water system, are the primary available freshwater resources on the earth and are sensitive to accelerated climate change and extensive human activities. Lakes play an important role in the terrestrial water cycle and biogeochemical cycle and substantially influence the health of humans living in the surrounding areas. Given the importance of lakes in the ecosystem, long-term monitoring of dynamic changes has important theoretical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Lake Bosten is the lowest point of the Yanqi Basin, located at the southern slope of the Tianshan Mountains. Its water area is vast, with an approximate length of 55 km and width of 25 km [28]. Bosten Lake is deep and dish-shaped with a flat bottom and a maximum water depth of approximately 14 m (Figure 1).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Lake Bosten is the lowest point of the Yanqi Basin, located at the southern slope of the Tianshan Mountains. Its water area is vast, with an approximate length of 55 km and width of 25 km [28]. Bosten Lake is deep and dish-shaped with a flat bottom and a maximum water depth of approximately 14 m (Figure 1).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Its main recharge river is the Kaidu River, and it is the main source of the Peacock River. Its source of recharge mainly comes from the glacier ice meltwater in the Tianshan region [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, future research needs to strengthen the simulation and analysis of regional-scale hydrological processes, such that the internal mechanism of lake evolution in sandy land can be clarified. It is important to highlight that our focus should not be limited to the in-depth study of a few representative lakes [3,30,31,43]. The continual and dynamic changes in small lakes within desertified areas, such as the Horqin Sandy Land, cannot be readily disregarded.…”
Section: Evolution Of Lakes In Sandy Landmentioning
confidence: 99%
“…Fan et al suggested that the annual fluctuation of water storage in Hulun Lake is mainly affected by precipitation [30]. In contrast, the reduction in the surface area of Bosten Lake is directly determined by the increase in annual average evaporation [31]. Temperature change plays a leading role in Selincuo Lake and Namucuo Lake [32].…”
Section: Introductionmentioning
confidence: 99%